THE ART OF DATA PROCESSING: ENSURING CLEAN AND ORGANIZED DATA FOR ANALYSIS - Suman Ankampally, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This thorough article examines how important data processing is to contemporary analytics and corporate operations. The article examines important facets of data preprocessing, such as feature engineering strategies, transformation techniques, and data cleaning methodologies. It examines the effects of different tools and technologies, paying special attention to distributed computing frameworks and Python-based solutions. Through in-depth case studies and industry analysis, the article shows how systematic data processing techniques greatly enhance operational effectiveness, model accuracy, and business outcomes. The article also looks at new developments in machine learning and artificial intelligence applications for data preparation. It provides firms looking to improve their data processing skills with best practices and insights into prospects.